0
$\begingroup$

I am really sorry for the junior question but I have a friend who does not understand this. I have been trying to explain this countless times but he does not understand and is convinced that $$(ms^{-1})^2$$ is (1) below instead of (2):

  1. $ms^{-2}$.
  2. $m^2s^{-2}$.
$\endgroup$
  • 2
    $\begingroup$ I edited to remove the large image; I hope that's fine with you. $\endgroup$ – Arturo Magidin Sep 13 '11 at 19:02
  • 2
    $\begingroup$ Since $x^2$ means $xx=x\times x$, then $$(ms^{-1})^2 = (ms^{-1})(ms^{-1}) = ms^{-1}ms^{-1} = mms^{-1}s^{-1} = m^2s^{-2}.$$ $\endgroup$ – Arturo Magidin Sep 13 '11 at 19:03
  • 5
    $\begingroup$ Does your friend understand the difference between $(ab)^2$ and $ab^2$? $\endgroup$ – Srivatsan Sep 13 '11 at 19:05
5
$\begingroup$

$$(a\cdot b)^2 = (a\cdot b)\cdot(a\cdot b)=a\cdot b\cdot a\cdot b=a\cdot a\cdot b\cdot b=a^2\cdot b^2$$

Now set $a=m$ and $b=s^{-1}$.

$\endgroup$
5
$\begingroup$

Perhaps it will help if you use an example: $m = 4$, $s=2$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.